2002
DOI: 10.1097/00007890-200211150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Vascularized islet-cell transplantation in miniature swine. I. Preparation of vascularized islet kidneys

Abstract: The implantation of islets beneath the autologous renal capsule permitted the establishment of a vascular supply and thereby supported normal islet-cell growth and function. The presence of thymic tissue beneath the autologous renal capsule facilitated the engraftment of minor-mismatched islets, and such grafts achieved results similar to autologous islet transplants. Therefore, the ability to create vascularized islet grafts may provide a strategy for successful islet transplantation across allogeneic and pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…28 It was suggested that this site allowed rapid establishment of a vascular network that contributed to long-term cell survival. However, hepatocytes alone, grafted under the kidney capsule, have not shown persistent survival.…”
Section: Discussionmentioning
confidence: 99%
“…28 It was suggested that this site allowed rapid establishment of a vascular network that contributed to long-term cell survival. However, hepatocytes alone, grafted under the kidney capsule, have not shown persistent survival.…”
Section: Discussionmentioning
confidence: 99%
“…22 At 3 months after the transplantation, tumors with the same histological features as the original thymomas in lck-pX rats occupied the transplanted thymus in the recipient kidney, indicating that thymomas can also develop at heterotopic sites if there is a thymic tissue.…”
Section: Malignant Transformation Of Thymoma In Rats T Tsuji Et Almentioning
confidence: 93%
“…The subcapsular space of the kidney may be a suitable site for tumor aggression where vascularization into the grafted tissues is easily introduced. 22 Actually, when tumor cells from the renal cell carcinoma were injected into subcutaneous, intraperitoneum, intravein or beneath the renal capsule of nude mice, a remarkable metastasis was observed only in cases where the cells were inoculated into the subcapsular space of the kidney. 24 In line with this, the thymomas could develop and become malignant with aggressive growth in the subcapusular space of the kidney, although development of a tumor was never found when original thymomas were transplanted into the retroperitoneal subserosal space (unpublished data).…”
Section: Malignant Transformation Of Thymoma In Rats T Tsuji Et Almentioning
confidence: 99%
“…Extension of the concept of composite organ transplantation to islets-kidneys A schematic of the preparation and testing of vascularized islet-kidneys (IK) in miniature swine [25] is shown in Fig. 2.…”
Section: Induction Of Tolerance To Renal Allografts In Miniature Swinementioning
confidence: 99%
“…Islet-kidneys (IK) were prepared by use of a paramedian or flank abdominal incision to expose the kidney, and injecting islets beneath the renal capsule using a 20G angiocatheter [25]. As for the previous thymic grafts, islets were allowed to heal for about 2 months prior to the intended date of allogeneic transplantation of the composite organ.…”
Section: Induction Of Tolerance To Renal Allografts In Miniature Swinementioning
confidence: 99%